Conceptual review between religiosity, work-life balance and employee performance of the employees in Higher Education Institutions (HEIs) / Mokana Muthu Kumarasamy … [et al.] - Kumarasamy, Mokana Muthu; Hasbolah, Farhana; Hamzah, Hanissah; Mohd Fazmi, Khairun Natasha; Omar, Siti Aisyah; Bhuiyan, Abul Bashar (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Working from Home (WFH) is now becoming a new normal and today it brings a big change in the way people think and act. This situation requires efficient remote tasks, availability of suitable facilities and equipment, time management, and the integrity of each one. However, some people find that working from home is a big challenge, especially for those with families and young children. This is not easy and it leads to stress and burdens because employees were not able to share good times with their family and work demands. Finding work-life balance occurs when individuals allocate mental, physical, and emotional resources in a way that can achieve personal and professional goals. It has to do with the ability of employees to manage their own job tasks, coordinate these tasks with employees, and take responsibility for the success or failure of these tasks. Within the context of higher education institutions (HEIs) in Malaysia the challenge is to monitor and supervise employees. This study aims to identify the influencing factors of work-life balance on employee performance and moderating effect of religiosity towards work-life balance and employee performance of HEIs. The study will be used to accumulate empirical literature by the name of religiosity towards work-life balance and employee performance in different online database sources such as Google Scholar, Springer Link, Wiley Blackwell, Science Direct, JSTOR, Emerald full text, SCOPUS, EBSCOHOST, etc. The review findings show that there is a significant effect of work- life balance especially, technological factors, institutional factors, individual factors are considered the most influential effects on employee performance. Moreover, the review study also identified that there is the moderating effect of religiosity towards work-life balance and employee performance of HEIs. The findings of the study will be used to develop a research framework for a rigorous in-depth study to draw policy guidelines for further improvements of work-life balance and employee performance in HEIs.